Sitagliptin Modulates the Response of Ovarian Cancer Cells to Chemotherapeutic Agents - Kosowska, Agnieszka (Int J Mol Sci, 2020)
The strong association between diabetes mellitus type 2 and cancer is observed. The incidence of both diseases is increasing globally due to the interaction between them. Recent studies suggest that there is also an association between cancer incidence and anti-diabetic medications. An inhibitor of dipeptidyl-peptidase 4 (DPP-4), sitagliptin, is used in diabetes treatment. We examined the influence of sitagliptin alone or in combination with a cytostatic drug (paclitaxel) on the development of epithelial ovarian cancer cells and the process of metastasis. We examined migration, invasiveness, apoptosis, and metalloproteinases (MMPs) and their inhibitors’ (TIMPs) production in two human ovarian cancer cell lines. Sitagliptin induced apoptosis by caspase 3/7 activation in paclitaxel-treated SKOV-3 and OVCAR-3 cells. Sitagliptin maintained paclitaxel influence on ERK and Akt signaling pathways. Sitagliptin additionally reduced migration and invasiveness of SKOV-3 cells. There were distinct differences of metalloproteinases production in sitagliptin-stimulated ovarian cancer cells in both cell lines, despite their identical histological classification. Only the SKOV-3 cell line expressed MMPs and TIMPs. SKOV-3 cells co-treated with sitagliptin and paclitaxel decreased concentrations of MMP-1, MMP-2, MMP-7, MMP-10, TIMP-1, TIMP-2. The obtained data showed that sitagliptin used with paclitaxel may be considered as a possibility of pharmacological modulation of intracellular transmission pathways to improve the response to chemotherapy.